Revelatory experiences as the beginning of Scripture: Paul’s Letters and the Prophets in the Hebrew Bible - Deines, Roland (Eisenbrauns, 2015)
What this article demonstrates is the close relation between revelatory events and their imprints in the biblical tradition. I have chosen the earliest writing in the New Testament to illustrate how quickly this process took place. Hardly more than a century passed between Jesus’ life and its understanding as the ultimate form of God’s revelation and its stabilization in authoritative writings which were regarded as equal to the Jewish Scripture (cf. 2 Peter 3:2, 15f.), with the first authoritative texts already in existence within 20 years after Jesus’ death. This happened without the influence of institutions, professional scribes, or established hierarchies. The message received its lasting meaning beyond the immediate reason for its composition through the authority of the messenger as a witness to the decisive revelatory event (cf. Acts 1:21f.; 2:32; 3:15; 10:39, 41; 13:31; 22:15; 1 Cor 9:1; 15:3-8; 1 Peter 5:1; 2 Peter 1:16-18; 1 John 1:1-3). It is worthwhile testing further whether these insights into the way the New Testament writings became Scripture might also shed some light on the genesis of the books of the Hebrew Bible.